A novel soil nutrient detection method based on combined ATR and DRIFT mid-infrared spectra. Issue 3 (10th January 2017) - Chen, Chen; Dong, Daming; Li, Zhiwei; Wang, Xiaoke
Abstract : A method which could both measure the ATR and DRIFT mid-infrared spectra of soils was developed. Combing the two types of spectra, the nutrients of soil were measured. Abstract : Conventional soil nutrient detection methods are time-consuming and laborious and cannot realize rapid measurement. Mid-infrared spectroscopy with the advantages of high detection speed, non-destructive testing, and a pretreatment-free process has been widely applied in soil nutrient analysis. In previous studies on the detection of soil compositions, diffuse reflection and attenuated total reflection are two commonly adopted ways in mid-infrared spectroscopy. In this paper, we developed a method which could simultaneously measure the infrared attenuated total reflection (ATR) and diffuse reflection infrared Fourier transform (DRIFT) spectra of soils, in order to obtain more abundant spectral information. We analyzed and predicted the contents of organic matters, organic carbon and total nitrogen quantitatively in soils by using chemometrics. The results showed that after combining ATR spectra and DRIFT spectra, the MSC-processed PLS models allowed a higher prediction accuracy than that of using ATR or DRIFT spectra alone. The coefficients of determination of organic matters, organic carbon and total nitrogen models were 0.93, 0.952 and 0.971, respectively. By combining ATR and DRIFT spectral information, the analytical ability of infrared spectroscopy was enhanced. This study provided a new method for the rapid measurement of soil nutrients.